The “Usefulness” Of the 360-degree Feedback System: A Consideration before Implementing the System - Ong, Ching Ying (INTI Publishing House Sdn. Bhd., 2007)
Performance appraisal is crucial in organizational management. Accuracy, fairness and effectiveness of a performance appraisal system are important to an effective evaluation result, which has influence on job satisfaction, motivation, and career development and performance management. There are few limitations that can undermine the accuracy, fairness and effectiveness of a performance appraisal system. However, these flaws can be minimized through several practices, such as: having the appraiser’s participation; generating inputs from different parties; adopting an appropriate Information gathering technique; and having knowledgeable appraisers Compared to a traditional performance appraisal system (or single-rate system), the 360-degree feedback system features greater accuracy, fairness and effectiveness. In addition, forces from business environment that cause changes in organizational structure, management style and job design have increased the popularity of the system. However, there is no assurance that the 360-degree feedback system is the best performance appraisal system, or even that It is a useful approach for every organization. In this paper, the term ‘appraiser(s)’ and appraise(s)’ will be adopted instead of ‘employer(s)’ (or ‘supervisors’) and ‘employee(s). This is to ensure the consistency in this essay, as in a 360.degree feedback system, appraisers can be employees and vice-versa.